Digitization of cultural heritage and copyright (Heritage, 2023)
The rapid technical and technological progress in the second half of the twentieth century led to the increasing use of computers in the economy and society and to the dominance of digital technology over the use of mechanical and electronic analog devices. Therefore, copyright has faced the challenge of how to regulate the digitization of copyrighted works, which in today's conditions is necessary for the development of innovation, science and knowledge transfer. The problem is that the increased technological possibilities have facilitated the reproduction of copyrighted works and their availability to the public via the Internet, so that copyright infringements occur online on a daily basis, and the scale of such infringements is enormous. As copyright is the foundation of the creative industry, because it encourages innovation, creation, investment in the creative industry and production, it is necessary to change the existing normative framework and adapt to the changes brought by the rapid development of technology.Attempts to legally regulate digitalization within the European Union in cases where there is no consent of the copyright holder began at the beginning of this century and continue to this day, facing numerous challenges brought by the modern age of the Internet and globalization. The European Union has approached this process very committedly, passing a large number of acts, primarily directives, which seek to enable the harmonization of copyright and related rights in the information society. In order to facilitate the process of preservation and dissemination of cultural heritage, it is necessary to implement in our law on copyright and related rights the solutions from the European Directive 2012/28 and Directive 2019/790.